Effectiveness of erlotinib as a second line therapy for patients with epidermal growth factor receptor (EGFR) mutation in non-small cell lung cancer (NSCLC): our clinical experience - Crvenkova, Simonida; Ivkovski, Lj; Dimovski, A; Kaeva, B (My University, 2012)
The aim of this study was to evaluate tumour response, QoL and adverse effects of erlotinib, EGFR tyrosine kinase inhibitor (TKI), as a second line therapy for patients with EGFR mutation in NSCLC, after failure of previous first-line therapy.